Middleware for Network Interoperability in IoT - Eko Sakti Pramukantoro; Fariz Andri Bakhtiar; Binariyanto Aji; Rasidy Pratama (IAES Indonesia Section, 2018)
One solution for interoperability issue in IoT is a middleware which is competent on resolving the problems of syntactical, semantic, and network interoperability. In previous study, a middleware capable of addressing semantic and syntactical interoperability challenges has been developed, yet has not responded to network interoperability matter. In this paper we continue our previous research by adding BLE and 6LoWPAN features to the middleware's communication media, so it may communicate with various devices. Interoperability test results show that the middleware is capable of responding to network interoperability challenges and able to receive data from multiple nodes simultaneously.